Culture medium pH influence on Gluconacetobacter physiology: Cellulose production rate and yield enhancement in presence of multiple carbon sources. (1st August 2016) - Yassine, Fatima; Bassil, Nathalie; Flouty, Roula; Chokr, Ali; Samrani, Antoine El; Boiteux, Gisèle; Tahchi, Mario El
Highlights: Gluconacetobacter physiology is studied in presence of different carbon sources. Bacterial cellulose yield is increased by the addition of acetic acid to the culture medium. Crystallinity of the polymer is evaluated in presence of different carbon sources. The effect of acetic acid as a co-carbon source for cellulose production is evaluated. Abstract: Gluconacetobacter genera are valued for bacterial cellulose (BC) and acetic acid production. BC is produced at optimal yields in classical microbiological media that are expensive for a large scale of production. In addition, BC usage for industrial purposes is limited due to low conversion rate into cellulose and to long incubation duration. In this paper, Gluconacetobacter isolated from apple vinegar was kinetically studied to evaluate cellulose production in presence of different carbon sources. Acetic and citric acid effect on Gluconacetobacter metabolism is clarified. It was shown that Gluconacetobacter uses glucose as a primary carbon source for cells growth and products formation. Acetic acid employment as a co-carbon source in Hestrin Schramm medium showed an increase of 17% in BC yield with a moderate decrease in the crystallite size of the resulting polymer.